Beyond Graphene: Chemistry of Group 14 Graphene Analogues: Silicene, Germanene, and Stanene - Hartman, Tomáš; Sofer, Zdeněk (ACS nano, 2019)
Two-dimensional materials have been extensively studied over the last two decades as they represent a class of materials with properties applicable in catalysis, sensing, optical devices, nanoelectronics, supercapacitors, and semiconductors. The properties of 2D materials can be tuned by exfoliation into mono- or few-layered systems and mainly by surface modification, which can result, for example, in altering the band gap or enhancing material stability toward degradation. This review focuses on the derivatization of group 14 layered materials beyond graphene silicene, germanene, and stanene and summarizes their preparation as well as chemical and physical properties. This review provides the current state-of-the-art in the field and provides a perspective for future development in the field of chemical derivatization of 2D materials beyond graphene.
Keywords: surface functionalization; exfoliation; germanene; polysiloxane; stanene; chemical modification; hydrogenation; germanane; silicene; silicane